2017
DOI: 10.1128/jvi.01579-17
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Recombinant Parainfluenza Virus 5 Expressing Neuraminidase Protects against Homologous and Heterologous Influenza Virus Challenge

Abstract: Seasonal human influenza virus continues to cause morbidity and mortality annually, and highly pathogenic avian influenza (HPAI) viruses along with other emerging influenza viruses continue to pose pandemic threats. Vaccination is considered the most effective measure for controlling influenza; however, current strategies rely on a precise vaccine match with currently circulating virus strains for efficacy, requiring constant surveillance and regular development of matched vaccines. Current vaccines focus on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Perhaps virus transmission from camels to humans can be blocked, with concomitant immunization of high-risk human populations, as proposed by CEPI (The Coalition for Epidemic Preparedness Innovations) and WHO. As a vaccine vector, PIV5 has been effective in mice, cotton rats, hamsters, guinea pigs, ferrets, dogs, and nonhuman primates (25,(46)(47)(48)(49). It will be worthwhile to test PIV5-MERS-S in camels in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps virus transmission from camels to humans can be blocked, with concomitant immunization of high-risk human populations, as proposed by CEPI (The Coalition for Epidemic Preparedness Innovations) and WHO. As a vaccine vector, PIV5 has been effective in mice, cotton rats, hamsters, guinea pigs, ferrets, dogs, and nonhuman primates (25,(46)(47)(48)(49). It will be worthwhile to test PIV5-MERS-S in camels in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to evaluate a combination of PIV5-113 and PIV5-NP as a candidate vaccine to increase the breadth of protection. Previously, we have tested PIV5-based candidate vaccines in mice, hamsters, guinea pigs, ferrets, dogs, and monkeys and found that PIV5-based candidate vaccines are effective in those animals ( 33 , [36] , [37] , [38] , 52 , [70] , [71] , [72] , [73] , [74] , [75] ). Importantly, this is the first report showing the efficacy of PIV5 as a vector for swine vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PIV5 viruses expressing NA of avian (H5N1) or pandemic (H1N1) influenza viruses were investigated. The results show that they can confer protection against homologous and heterologous influenza virus challenge in mice . In the case of PIV5 expressing NA of H5N1, two vaccine doses even conferred sterilizing immunity against H5N1 infection in mice.…”
Section: Piv5‐vectored Vaccines Against Human and Animal Infectious Dmentioning
confidence: 93%
“…In the case of PIV5 expressing NA of H5N1, two vaccine doses even conferred sterilizing immunity against H5N1 infection in mice. Both vaccines were also able to reduce clinical signs of disease and influenza virus shedding in ferrets. This study indicates that PIV5 expressing NA has the potential to be exploited as a universal influenza vaccine.…”
Section: Piv5‐vectored Vaccines Against Human and Animal Infectious Dmentioning
confidence: 99%